Ultrasound assessment of the inferior vena cava in children: A comparison of sub‐xiphoid and right lateral coronal views. Issue 4 (1st October 2021) - Yamaguchi, Yoshikazu; Moharir, Alok; Kim, Stephani S.; Wakimoto, Mayuko; Burrier, Candice; Shafy, Shabana Z.; Hakim, Mohammed; Tobias, Joseph D.
Abstract: Objectives: The inferior vena cava collapsibility index (IVCCI) has been used to assess the respiratory variation of the inferior vena cava (IVC) diameter and hence intravascular volume. The sub‐xiphoid view (SXV) is the standard view to evaluate the IVC. The right lateral transabdominal view (RLV) has been shown in adults to be an alternative view to evaluate the IVC when the SXV is not feasible. The aim of the study was to compare IVC dimensions from these two views and thus determine whether the RLV view can be used instead of the SXV in pediatric patients. Methods: We conducted a single‐center prospective observational crossover study. Study subjects were ASA physical status 1–2 children, 1–12 years of age scheduled for elective surgery under general anesthesia. Anesthesia was maintained by mask with spontaneous ventilation with end‐tidal sevoflurane at 2%–5% after the induction of anesthesia. IVCCI was measured using M‐mode in both the SXV and RLV. Results: The study cohort included 50 children with a mean age of 5.1 years. The median value for the IVCCI‐sx was 0.45 (IQR: 0.28–0.70) while the IVCCI‐rl was 0.30 (0.19–0.5). The mean difference between the two groups was 0.12 (95% CI: 0.177–0.066, p < .001, two‐tailed paired t ‐test). Spearman's rank correlation coefficient was 0.66. The univariate linear regression model was IVCCIsx = 0.21 + 0.77 × IVCCIrl. Conclusions: IVCCIrl was lower than IVCCIsx. IVCCI measured from the right lateral view tended to overestimate the patient's fluid‐responsiveness and therefore these two values are not interchangeable. Abstract : Transverse views of the great arteries. IVC, inferior vena cava; dAo, descending aorta; VB, vertebral body.